2015
DOI: 10.5423/ppj.oa.02.2015.0024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerated Compost Tea on the Growth Promotion of Lettuce, Soybean, and Sweet Corn in Organic Cultivation

Abstract: This study investigated the chemical characteristics and microbial population during incubation of four kinds of aerated compost teas based on oriental medicinal herbs compost, vermicompost, rice straw compost, and mixtures of three composts (MOVR). It aimed to determine the effects of the aerated compost tea (ACT) based on MOVR on the growth promotion of red leaf lettuce, soybean and sweet corn. Findings showed that the pH level and EC of the compost tea slightly increased based on the incubation time except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
73
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 36 publications
12
73
0
3
Order By: Relevance
“…Some of these metabolites may act against increasing the number of leaves at high concentrations of CT. These results are in agreement with Kim et al (2015), who revealed that, the red leaf lettuce treated with F spray and with higher CT concentration was less effective in increasing the number of leaves than in the lower CT concentration. Integrated treatment of SD with SS at 25% CT significantly increased the number of leaves.…”
Section: Effect Of Compost Tea On the Number Of Leavessupporting
confidence: 93%
“…Some of these metabolites may act against increasing the number of leaves at high concentrations of CT. These results are in agreement with Kim et al (2015), who revealed that, the red leaf lettuce treated with F spray and with higher CT concentration was less effective in increasing the number of leaves than in the lower CT concentration. Integrated treatment of SD with SS at 25% CT significantly increased the number of leaves.…”
Section: Effect Of Compost Tea On the Number Of Leavessupporting
confidence: 93%
“…The transformation and reuse of composting leachates would bring environmental benefits through the planting of green areas, which would in turn help contain and limit erosion while also increasing carbon sequestration. Furthermore, compost leachates can replace chemical fertilizer in organic cultivation farms (Kim et al 2015). Nevertheless, these alternative approaches have certain obstacles to overcome before becoming technically feasible.…”
Section: Composting Leachate Reuse and Transformationmentioning
confidence: 99%
“…and plants were inoculated with AMF and moderate P rate (7.5 mg l -1 ) produced larger tubers than non-inoculated plants. Scagel and Schreiner (2006) concluded that on soybean treated with compost tea was more effective an increasing the root nodule formation by 7.25 times than untreated with compost tea and promoted the growth of root and shoot of both soybean and sweet corn, as these results indicated that aerated compost tea (ACT) could be used as liquid nutrient fertilizer with active microorganisms ( Kim et al, 2015).…”
Section: Shoots Number Per Clump Leaf Area and Leaf Blade Lengthmentioning
confidence: 99%